ChemInform Abstract: Total Syntheses of Echinopines A and B, Sesquiterpenes with a Unique Tetracyclic [3‐5‐5‐7] Skeleton. Issue 29 (June 2016) - Sanogo, Youssouf; Allievi, Luca; Lecourt, Camille; Dhambri, Sabrina; Ardisson, Janick; Sorin, Geoffroy; Lannou, Marie‐Isabelle
Abstract: Review: 30 refs.